Identification and functional importance of plasma kallikrein in the synovial fluids of patients with rheumatoid, psoriatic, and osteoarthritis. Issue 5 (May 1995) - Rahman, M M; Bhoola, K D; Elson, C J; Lemon, M; Dieppe, P A
Abstract : OBJECTIVES--To determine and identify, unequivocally, if plasma kallikrein (PK) is present in the synovial fluid of patients with rheumatoid (RA), psoriatic (PA) and osteo (OA) arthritis, and to consider its functional importance in the inflamed joint. METHODS--Therapeutically aspirated synovial fluids (pooled and individual samples, n = 66) were obtained from patients with arthritis. In addition, serum (n = 14) was collected from RA patients, and saliva (n = 10) and urine (n = 10) from normal individuals. Enzymic (amidase) and immunoreactive activities of PK and its precursor, prokallikrein (PPK), were determined. The presence of PK was assessed by incubation with soya bean trypsin inhibitor (SBTI), and by adsorption with anti-PK antibody linked to Sepharose. An enzyme-linked immunosorbant assay (ELISA) for PK was developed for quantitative measurement of total PK in biological fluids. Enhancement of the PK dose-response by RA synovial fluid made it necessary to remove RF from synovial fluids before determination of PK by ELISA. RESULTS--Amidase activity was demonstrated in synovial fluid pools and shown to be inhibited completely by SBTI, and removed by prior treatment with anti-PK Sepharose. Total PK activity (PK + PPK) from individual synovial fluid specimens did not differ significantly between patients with RA (median activity 76 mU/g protein), PA (80 mU/g protein) or OA (60 mU/g protein). Similar results were obtained when active PK alone was measured. No correlation was found between active PK or total PK values and the severity score for individual joints. Most of the measured immunoreactivity was removed by adsorption with anti-PK antibody linked to Sepharose. CONCLUSION--The results support the hypothesis that plasma kallikrein is present in synovial fluid. The enzyme may be important in the pathogenesis of inflamed joints.